Status of ToRCH positivity among the children presented with congenital Hydrocephalus (Bangladesh Journal of Neurosurgery, 2020)
Introduction: ToRCH is an acronym for four congenital infections that are sometimes difficult to distinguish: Toxoplasmosis, Rubella, Cytomegalovirus (CMV), and Herpes Simplex Virus (HSV). This group of organisms produces serious Central Nervous System (CNS) and other infections, which are potentially preventable and treatable.Methods: Neonates and infants with hydrocephalus (N = 65) identified via the outpatient department of the National Institute of Neurosciences and Hospital (NINS&H), were prospectively screened for ToRCH antibodies. Hydrocephalus secondary to Tumor or Trauma was excluded from this study.Results: Evidence of 75.38 % (p =